Issues in Upper Secondary Science Education : Comparative Perspectives - Vlaardingerbroek, Barend; Taylor, Neil; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
This book provides a comparative look at key issues that characterize and contextualize upper secondary science education in sixteen countries in Oceania, South America, Asia, Europe, North America, Africa, and the Middle East, incluing links with elementary and early science, final assessment, and the secondary/tertiary education interface.
Keywords: Science; Science, general